The Association between Body Mass Index and Mortality on Peritoneal Dialysis: A Prospective Cohort Study. Issue 4 (June 2014) - Kim, Yong Kyun; Kim, Su-Hyun; Kim, Hyung Wook; Kim, Young Ok; Jin, Dong Chan; Song, Ho Chul; Choi, Euy Jin; Kim, Yong-Lim; Kim, Yon-Su; Kang, Shin-Wook; Kim, Nam-Ho; Yang, Chul Woo
Background: Previous studies have demonstrated that increased body mass index (BMI) is associated with decreased mortality in hemodialysis (HD) patients. However, the association between BMI and survival has not been well established in patients undergoing peritoneal dialysis (PD). The aim of the study was to determine the association between BMI and mortality in the PD population using the Clinical Research Center (CRC) registry for end-stage renal disease (ESRD) cohort in Korea. Methods: Prevalent patients with PD were selected from the CRC registry for ESRD, a prospective cohort study on dialysis patients in Korea. Patients were categorized into four groups by quartiles of BMI. Cox regression analysis was used to calculate the adjusted hazard ratio (HR) of mortality with a BMI of quartile 2 (21.4 - 23.5 kg/m 2 ) as the reference. Results: A total of 900 prevalent patients undergoing PD were included. The median follow-up period was 24 months. The multivariate Cox proportional hazard model showed that the lowest quartile of BMI was associated with higher mortality (HR 3.00, 95% confidence interval (CI), 1.26 - 7.15). However, the higher quartiles of BMI were not associated with mortality compared with the reference category of BMI quartile 2 (Quartile 3: HR 1.11, 95% CI, 0.43 - 2.85, Quartile 4: H R 1.64, 95% CI, 0.66 - 4.06) after adjustment for clinical variables. Conclusions: Lower BMI was a significant risk factor for death, but increased BMI was not associated with mortality in Korean PD patients.